Development of hydrophilic nanocarriers for the charged form of the local anesthetic articaine - Silva de Melo, Nathalie Ferreira [UNESP]; Ramos Campos, Estefania Vangelie [UNESP]; Goncalves, Camila Morals; Paula, Eneida de; Pasquoto, Tatiane; Lima, Renata de; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier B.V., 2014)
One of the current challenges in drug encapsulation concerns the development of carrier systems for hydrophilic compounds. Potential carriers include nanocapsules prepared with amphiphilic polymers, which consist of a polymeric coating surrounding an aqueous nucleus, or dense matrices such as nanospheres of alginate/chitosan, where the drug may be dispersed in the matrix or adsorbed on the surface. The development of new formulations of nanocarriers, for example the poly(ethylene glycol)-poly(epsilon-caprolactone) (PEG-PCL) nanocapsules and alginate/chitosan (AG/CS) nanospheres described in this work, is needed in the case of ionized drugs such as articaine. This amino amide local anesthetic is the drug of choice in dentistry for regional anesthesia as well as the relief of acute and chronic pain. Here, the physico-chemical properties of suspensions of the nanoparticles (considering diameter, polydispersion, and zeta potential) were determined as a function of time, in order to establish the stability of the systems. The formulations did not show any substantial changes in these parameters, and were stable for up to 120 days of storage at ambient temperature. Satisfactory encapsulation efficiencies were obtained for the PEG-PCL nanocapsules (60%) and the AG/CS nanospheres (45%). Cytotoxicity assays confirmed that the encapsulation of articaine reduced its toxicity, relative to the free drug. The most promising results were obtained using the vesicular system (PEG-PCL nanocapsules), which not only altered the release profile of the drug, but also resulted in the lowest toxicity. This carrier system therefore holds promise for use in future practical applications. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Polymeric nanoparticles; PEG-PCL copolymer; Alginate/chitosan; Local anesthetic; Articaine